2023
DOI: 10.1186/s12958-023-01139-w
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes of oxidative stress and PON1 lactonase activity and status in older pregnant women undergoing assisted reproductive technology: a prospective nested case-control study

Chenyu Jiang,
Meng Chen,
Yujie Wu
et al.

Abstract: Background Childbearing in women with advanced maternal age (AMA) has increased the need for artificial reproductive technology (ART). ART and oxidative stress are associated with many pregnancy complications. Paraoxonase (PON) 1 is one of the key components responsible for antioxidative activity in high-density lipoprotein (HDL). This study aimed to investigate the longitudinal changes of oxidative stress and PON1 lactonase activity and status in older women undergoing ART. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Recent studies have demonstrated that genetic variations in the PON1 gene cause significant effects on its enzyme activity [21][22][23]. For instance, the PON1 variant with glutamine at position 192 increases the protein's ability to prevent the breakdown of oxidized lipids and shield LDL from oxidative changes [24].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that genetic variations in the PON1 gene cause significant effects on its enzyme activity [21][22][23]. For instance, the PON1 variant with glutamine at position 192 increases the protein's ability to prevent the breakdown of oxidized lipids and shield LDL from oxidative changes [24].…”
Section: Introductionmentioning
confidence: 99%